Budidaya Ikan dalam Ember Sebagai Bentuk Pemanfaatan Lahan Pekarangan di Kelurahan Wonorejo - Nashania Rohmah, Naswah; Ayu Bramasari, Nadya; Harya, Gyska Indah (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This community service program was carried out to address the challenge of limited productive land in RW 02 RT 05, Wonorejo, Surabaya, with the main objective of improving residents’ ability to utilize narrow home yards through the implementation of fish cultivation in buckets. The program was conducted using a direct practical approach, beginning with bucket media preparation, water pipe installation, stocking catfish fingerlings, planting water spinach, and followed by regular water monitoring and plant maintenance. A total of four cultivation buckets were successfully installed, containing 120 catfish fingerlings and 25 water spinach seedlings, all of which were collectively managed by local residents. The implementation results indicated an increase in residents’ understanding of household-scale cultivation techniques, marked by a catfish survival rate of over eighty percent and rapid water spinach growth showing significant development within one week. The benefits gained were not only in the form of increased knowledge and hands-on experience, but also in the productive use of previously unused yard space. Based on these achievements, it can be concluded that this program successfully encouraged active community involvement in small-scale food cultivation and helped foster new productive, sustainable habits that support household food security in urban areas.